How to Optimize the Allocation of Anti-epidemic Materials in Public Health Emergencies From the Perspective of Public Economics - Tang, Ziqi; Wang, Zhengyi; An, Yixuan (Frontiers in Psychology, 2022)
During the COVID-19 public health crisis, market failures such as shortage of supplies and soaring prices of anti-epidemic materials – with masks as the core – have occurred. In essence, such anti-epidemic materials have the dual nature of necessities with low elasticity of demand and private products with positive externalities. This research explores the understanding of anti-pandemic materials and how different initiatives, and evaluation to increase availability of necessary resources can be effective in curbing a pandemic. Market regulation results in a non-Pareto optimal allocation of resources and the difficulty of exerting the positive externalities of products. However, in China, the market failure of anti-epidemic materials was quickly resolved, due to the institutional advantages of socialism with Chinese characteristics, the social responsibility drive of domestic enterprises, and cultural genes that focus on equity and concern for the disadvantaged. The optimal allocation of anti-epidemic materials gave access to exerting efficiency and fairness effects, positive external effects, and public effects.